Master of the Masquerade: An Atypical Presentation of Acute Aortic Dissection - Ramy Mando; Daniel Tim; Anthony DeCicco; Justin Trivax; Ivan Hanson (Case Reports in Cardiology)
Acute aortic dissection (AAD) is associated with unacceptably high mortality rate. As such, early diagnosis and aggressive management are essential in order to avoid life-threatening complications. Herein, we report an atypical presentation of AAD and clinical sequelae.